If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 1) = -32 Reorder the terms: -10(1 + s) = -32 (1 * -10 + s * -10) = -32 (-10 + -10s) = -32 Solving -10 + -10s = -32 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -10s = -32 + 10 Combine like terms: -10 + 10 = 0 0 + -10s = -32 + 10 -10s = -32 + 10 Combine like terms: -32 + 10 = -22 -10s = -22 Divide each side by '-10'. s = 2.2 Simplifying s = 2.2
| 5x^3+15x^2+8x+6=0 | | -4.9t^2+92t-141=0 | | (x-9)(x-1-3i)(x-1+3i)=0 | | 2n+n+6n+2=11 | | 3-2ax-2/3a-2/3x | | 13r+-4r+-12=6 | | 14w=9w+35 | | Y=4x^2+196-11 | | m^-5/2=1/2048 | | 5(3)-3y=3 | | 11y-5=2y+24 | | X+5+60+x=180 | | 2x+x+40+x+20=180 | | 54x+5y-5z=91 | | 1.37=(x^3)/(x^2) | | 16b-12-3b=14 | | 36-x=8 | | f(x)=f(x-4)+f(2x-1) | | 14x+-13x=7 | | 12y-7y=45 | | 2(s-5)-6=4 | | 28+(8+x)=36 | | x^5=5x^4 | | 3(d-4)+1=10 | | 2x+57=119 | | 2(g+2)=6 | | -3u-11u=-14 | | -15g+3g=12 | | 3(u+1)+1=13 | | 34=2y+8 | | 14-2f=10 | | 5w+1.5=4.5 |